1985
DOI: 10.1152/jappl.1985.59.1.229
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nicotine in cigarette smoke on acute ventilatory responses in awake dogs

Abstract: To determine whether the acute ventilatory responses to inhaled cigarette smoke are affected by a difference in nicotine level, control cigarettes (low-nicotine research cigarettes) were laced with nicotine to generate an increase of 330% (mean) in nicotine content with little or no change in the levels of other smoke constituents. Acute ventilatory responses to both control and nicotine-laced cigarettes were determined and compared in six awake chronic dogs. Spontaneous inhalation of nicotine-laced cigarette … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Whereas, coughing was absent with inhalation of both low nicotine and gas phase irritants. This corroborated their findings in the dog model (Lee et al, 1983(Lee et al, , 1985(Lee et al, , 1986(Lee et al, , 1989Kou & Lee, 1990. The second study assessed the role of nicotine in TS-associated airway irritation and cough.…”
Section: Mechanisms Of Action Of Ts In Acute Cough 321 Nicotinic Resupporting
confidence: 70%
See 1 more Smart Citation
“…Whereas, coughing was absent with inhalation of both low nicotine and gas phase irritants. This corroborated their findings in the dog model (Lee et al, 1983(Lee et al, , 1985(Lee et al, , 1986(Lee et al, , 1989Kou & Lee, 1990. The second study assessed the role of nicotine in TS-associated airway irritation and cough.…”
Section: Mechanisms Of Action Of Ts In Acute Cough 321 Nicotinic Resupporting
confidence: 70%
“…Using single fibre analysis, the authors observed that a single puff of TS generated from high nicotine, but not low nicotine cigarettes triggered action potential generation in bronchopulmonary C-fibres and RARs. Moreover, the competitive selective nACh receptor antagonist hexamethonium inhibited sensory nerve stimulation in response to TS, but had no effect on other tussive stimuli, indicating a role for nicotine in the smokeinduced irritant response in dogs (Lee et al, 1983(Lee et al, , 1985(Lee et al, , 1986(Lee et al, , 1989Kou & Lee, 1990. The ability of nicotine to stimulate airway sensory nerves was corroborated in rat isolated vagal ganglia neurons by assessing calcium influx.…”
Section: Mechanisms Of Action Of Ts In Acute Cough 321 Nicotinic Rementioning
confidence: 96%
“…The effects of nicotine on chemoreflex sensitivity in humans are unknown. Some, but not all, [21][22][23] animal studies have been able to show that nicotine increases peripheral chemoreceptor sensitivity to hypoxia. 24 -26 This is likely because of the fact that the effects of exogenous nicotine on chemoreceptors depend on the predominance of nicotinic and muscarinic receptors on the carotid bodies.…”
mentioning
confidence: 99%
“…Nicotinic receptors have been also located on the other side of the chemosensitive synapse 15 but the role of the latter in the carotid body neurotransmission remains unclear. Moreover, several animal studies have shown that nicotine induces an excitatory effect on sympathetic drive mediated by peripheral chemoreflex stimulation 16,17 . However, these results can not be generalized, 18 possibly as a result of differences among species in the predominance of nicotinic receptors on the carotid bodies 14,19 .…”
Section: Autonomic Effects Of Nicotinementioning
confidence: 99%